2002
DOI: 10.1097/00006123-200208000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Tumor Cooperative Group NIH Trial 87-01: A Randomized Comparison of Surgery, External Radiotherapy, and Carmustine versus Surgery, Interstitial Radiotherapy Boost, External Radiation Therapy, and Carmustine

Abstract: We conclude that there is no long-term survival advantage of increased radiation dose with (125)I seeds in newly diagnosed glioma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Although prior retrospective studies have documented a modest survival advantage with the addition of SRS delivered using various technologies, 14,23,24,27,29,32,34,39 others have found no added benefit. 4,9,16,37,38 A single prospective randomized trial by the Radiation Therapy Oncology Group (RTOG 93-05) 42 found no improvement in overall survival (OS) when various forms of linear acceleratorand Gamma Knife-based SRS were given prior to conventional fractionated RT. 15 That study was not designed to evaluate the potential role of SRS at the time of GBM progression in patients who had received standard of care initial management.…”
mentioning
confidence: 99%
“…Although prior retrospective studies have documented a modest survival advantage with the addition of SRS delivered using various technologies, 14,23,24,27,29,32,34,39 others have found no added benefit. 4,9,16,37,38 A single prospective randomized trial by the Radiation Therapy Oncology Group (RTOG 93-05) 42 found no improvement in overall survival (OS) when various forms of linear acceleratorand Gamma Knife-based SRS were given prior to conventional fractionated RT. 15 That study was not designed to evaluate the potential role of SRS at the time of GBM progression in patients who had received standard of care initial management.…”
mentioning
confidence: 99%
“…One large randomized study by Selker and colleagues with 270 patients examined the use of interstitial brachytherapy in newly diagnosed high grade glioma 40 . Patients were randomized to two groups, one receiving resection, external beam radiation, and chemotherapy with the other group receiving resection, external beam radiation, chemotherapy, and 125 I permanent interstitial brachytherapy.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…After thorough analysis, these studies have failed to show significant benefits in terms of time to progression (TTP) or overall survival (OS) in these patients, including patients in two randomized controlled trials (Laperriere et al, 1998;Selker et al, 2002). Furthermore, a relevant number of radiation-induced necroses requiring subsequent surgical resection were described, which is attributed to the predominantly high activity/high dose rate implantation regimens chosen due to the high proliferation rate of these tumors.…”
Section: Sbt For High-grade Gliomas (Who III and Iv)mentioning
confidence: 99%